STRATEGI PENINGKATAN PERAN STAKEHOLDER DALAM PENGELOLAAN MANGROVE DI KABUPATEN TANGERANG - Muzani Muzani (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2014)
ABSTRACT Mangrove ecosystems have important ecological, economic and social functions that need consideration in coastal development. Mangroves in Tangerang District are being degraded by human activities brought about by a range of stakeholders. The complexity of stakeholders creates problems through various government departments having overlapping jurisdictions. This study aimed to develop strategies to increase the role of stakeholders in the management of mangrove ecosystems in Tangerang regency. Stakeholders were identified from interviews obtained through a snowball sampling method. In the coastal district of Tangerang there are 13 different types of stakeholders involved in mangrove management from government to local people. Each of these stakeholders has an interest and influence in mangrove management. Lack of coordination among stakeholders often results in a variety of management activities. The study recommends strategies to increase the role of stakeholders through improved coordination, information and collaboration among stakeholders. Keywords: stakeholders, management, mangrove.